Fast and Scalable Relational Division on Database Systems - Gonzaga, André S.; Cordeiro, Robson L. F. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2016: Anais do XXXI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2016.24323, 2016)
The Relational Algebra is composed of several operators to assist queries and data manipulation on Relational Databases. The Relational Division operator, particularly, allows simple representations of several queries involving the concept of “for all”, however, the SQL does not have an explicit implementation for it. In this paper, we compare the performance of the best implementation known for the division operator in SQL, considering different cases of use. We also present a new algorithm for the division, which we implemented through stored procedures. We performed a case study using the relational division to select genetic data. The results showed that our implementation for the relational division is potentially faster than the best implementation in SQL.